Use Of Learning Media Based On Powerpoint In Improving Students' Understanding Of Grade X Economics Subject - Jerico Rinaldi Sillaban; Dearlina Sinaga; Elisabeth Margareta (STABN RADEN WIJAYA WONOGIRI, 2024)
This study was conducted to determine the effect of using PowerPoint-based learning media on the understanding of 10th grade students in Economics at Parulian 2 Private High School, Medan. The background of this study is the low level of students' understanding of Economics material, as indicated by the results of observations of declining grades in the last three years. One of the contributing factors is the less than optimal use of learning media by teachers, where the lecture method still dominates, making students passive and less motivated. The type of research used is quantitative research with an experimental design using a two-group pretest-posttest design. The subjects of the study were 28 students in class XA as the experimental class who were given treatment with animated PowerPoint media, and 27 students in class XB as the control class who were taught with conventional lecture methods. The research instruments consisted of an understanding test, teacher and student observation sheets, and an understanding questionnaire. The data were analyzed using descriptive statistical tests, normality tests, and simple regression tests. The results showed that there was a significant increase in students' understanding after using PowerPoint learning media. The average student comprehension score in the experimental class increased from 61.48 in the pretest to 86.50 in the posttest, while the control class only increased from 66.10 to 71.50. This demonstrates that the use of PowerPoint-based learning media can improve student comprehension more effectively than lecture methods. Therefore, it can be concluded that PowerPoint-based learning media has a positive effect on improving student comprehension in Economics. This research is expected to serve as a reference for teachers in developing more innovative and engaging learning strategies tailored to student needs